Insights on the catalytic behaviour of sulfonic acid-functionalized ionic liquids (ILs) in transesterification reactions – voltammetric characterization of sulfonic task-specific ILs with bisulfate anions. Issue 4 (25th January 2021) - Martini, María B.; Fernández, José L.; Adam, Claudia G.
Abstract : Cyclic voltammetry measurements on imidazolic ionic liquids with sulfonic acid groups and bisulfate counterions revealed that they work as efficient reservoirs of sulfuric acid and are able to dose it on demand to uphold an efficient acid catalysis. Abstract : This work shows for the first time the link between the amount of free sulfuric acid (as detected by cyclic voltammetry) and the activity of sulfonic-acid-functionalized ionic liquids (ILs) as acid catalysts for a transesterification reaction, and demonstrates that sulfonic acid groups, while are not directly involved in the catalysis, release the free acid during the reaction. Two imidazolic ILs with bisulfate as the counterion and their corresponding task-specific ILs (TSILs) that resulted from the addition of a sulfonic acid group inside the imidazolic-base structure were studied. The outstanding catalytic activity at room temperature of the TSILs 1-(4-sulfonic acid)-butyl-3-methylimidazolium bisulfate ([bsmim]HSO4 ) and 1-(4-sulfonic acid)-butyl-imidazolium bisulfate ([bsHim]HSO4 ) for the transesterification of p -nitrophenyl acetate with methanol was associated to the significant amounts of free sulfuric acid in equilibria with the ionic pairs. It was concluded that these TSILs function as reservoirs for releasing the free acid, which is the actual acid catalyst. In contrast, the corresponding non-sulfonic ILs supply very little amounts of free acid and consequently present low catalytic activities at room temperature, which in fact can be improved by increasing the reaction temperature up to 100 °C.